NILAI PENDIDIKAN ISLAM DALAM GURINDAM DUA BELAS KARYA RAJA ALI HAJI - Ilyas, Ilyas; H. Putera, Griven; Muliardi, Muliardi (Universitas Lancang Kuning, 2020)
This writing analyzes values an Islamic teaching by focusing on a text Gurindam Dua Belas written by Raja Ali Haji. The result shows that Gurindam Dua Belas containing many Islamic values which is the actualization of Al Qur’an and Hadist as the main source of Islamic teaching. From the discussion, it is found out that the Islamic values contained in Gurindam Dua Belas are very comprehensive which covers the core of the basic teaching of Islam. The basic values consist of Ilahiyah value and insyaniyah value. The primary Ilahiyah value deals with faith (Iman), Islam, ihsan, taqwa, ikhlas, tawwakal, patient, and syukur (thankful). The insaniyah value consists of silaturahmi, ukhuwah, iffah, qawamiyah, and munfiqun. Those values bear noble akhlak reflected in attitudes and daily behaviors.